Clustered DNA double-strand break formation and the repair pathway following heavy-ion irradiation. (22nd November 2018) - Hagiwara, Yoshihiko; Oike, Takahiro; Niimi, Atsuko; Yamauchi, Motohiro; Sato, Hiro; Limsirichaikul, Siripan; Held, Kathryn D; Nakano, Takashi; Shibata, Atsushi
Abstract: Photons, such as X- or γ-rays, induce DNA damage (distributed throughout the nucleus) as a result of low-density energy deposition. In contrast, particle irradiation with high linear energy transfer (LET) deposits high-density energy along the particle track. High-LET heavy-ion irradiation generates a greater number and more complex critical chromosomal aberrations, such as dicentrics and translocations, compared with X-ray or γ irradiation. In addition, the formation of >1000 bp deletions, which is rarely observed after X-ray irradiation, has been identified following high-LET heavy-ion irradiation. Previously, these chromosomal aberrations have been thought to be the result of misrepair of complex DNA lesions, defined as DNA damage through DNA double-strand breaks (DSBs) and single-strand breaks as well as base damage within 1–2 helical turns (<3–4 nm). However, because the scale of complex DNA lesions is less than a few nanometers, the large-scale chromosomal aberrations at a micrometer level cannot be simply explained by complex DNA lesions. Recently, we have demonstrated the existence of clustered DSBs along the particle track through the use of super-resolution microscopy. Furthermore, we have visualized high-level and frequent formation of DSBs at the chromosomal boundary following high-LET heavy-ion irradiation. In this review, we summarize the latest findings regarding the hallmarks of DNA damage structure and the repair pathway following heavy-ion irradiation. Furthermore, we discuss the mechanism through which high-LET heavy-ion irradiation may induce dicentrics, translocations and large deletions.